THE RIGHT TO FREEDOM OF EXPRESSION VIS ÁVIS PUBLIC INTEREST - Veljanoska, Svetlana (Journal of process management and new technologies, 2016)
The right to freedom of expression is one of the fundamental human rights. This, among other things, is guaranteed by Article 10 of the European Convention. However, the freedom of expression is not an absolute right, which means that in some situations it may be restricted, especially if the public interest requires that. Submission of information for media coverage must be in accordance with the rights of the people who are involved. These rights are guaranteed by the European Convention on Human Rights and Freedoms, by the Constitution and by Laws. Having in consideration that these freedoms carry some duties, the enjoyment of these freedoms may be based on formalities, conditions, restrictions or penalties, as it is prescribed by law and they are necessary in one democratic society in behalf of crime prevention, protection of reputation or protection of the rights of other people, for prevention of disclosure of confidential information or for maintaining the authority and independence of the judiciary. If the courts accept the thesis that somebody has the right to say or write something and it is said in public interest, although it violates the rights of another person, it means that the freedom of expression prevails over some other rights. This paper aims to examine the aspect of freedom of expression, especially in the media and the judiciary, versus the need of protection of the public interest and the latest legal decisions that relate to this matter.